2023
DOI: 10.3389/fmicb.2023.1200997
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes in the context of developing sustainable intensified aquaculture

Abstract: With an ever-growing human population, the need for sustainable production of nutritional food sources has never been greater. Aquaculture is a key industry engaged in active development to increase production in line with this need while remaining sustainable in terms of environmental impact and promoting good welfare and health in farmed species. Microbiomes fundamentally underpin animal health, being a key part of their digestive, metabolic and defense systems, in the latter case protecting against opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…The HBW samples all have similar microbiomes, and therefore may be considered as an indicator of a standard microbial membership and composition for healthy sea urchins in our aquarium. However, it should be noted that a single “healthy” microbiome likely does not exist, as a major characteristic of a healthy microbiome is its ability to be dynamic [ 23 ]. Nonetheless, because the microbiomes of the DBW samples differ from those of the HBW samples (regions of non-lesioned tissue) from sea urchins in the same aquarium, this indicates that the spotting disease infection affects surface areas of the sea urchin that are outside of the observable lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBW samples all have similar microbiomes, and therefore may be considered as an indicator of a standard microbial membership and composition for healthy sea urchins in our aquarium. However, it should be noted that a single “healthy” microbiome likely does not exist, as a major characteristic of a healthy microbiome is its ability to be dynamic [ 23 ]. Nonetheless, because the microbiomes of the DBW samples differ from those of the HBW samples (regions of non-lesioned tissue) from sea urchins in the same aquarium, this indicates that the spotting disease infection affects surface areas of the sea urchin that are outside of the observable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have focused on identifying the causative agent underlying spotting disease, which suggests a wide array of pathogenic bacteria, few studies have reported an analysis of microbiomes of tissues from sea urchins infected with spotting disease [ 5 ]. Furthermore, none report the microbiome of tissues from sea urchins housed in a closed aquarium system, which have distinct properties and dynamics compared to open aquarium systems, leading to direct impacts on the host microbiome [ 23 ]. Because the microbiome on sea urchins shifts when transferred from the ocean to a closed aquarium [ 24 ], sampling sea urchins housed in the same aquarium system allows direct comparisons among the microbiome samples.…”
Section: Introductionmentioning
confidence: 99%
“…This study is not intended to offer an exhaustive review of the existing literature on these subjects. A more comprehensive exploration of these themes can be found in recent review articles [35,36]. The current paper aims to emphasize the key discoveries derived from our research employing genetic and genomics methodologies to enhance disease resistance, focusing on three principal aquaculture species: white leg shrimp (Litopenaeus vannamei), striped catfish (Pangasianodon hypophthalmus), and yellowtail kingfish (Seriola lalandi).…”
Section: Introductionmentioning
confidence: 99%
“…It plays an increasingly important role in the global food supply. [2][3][4] Infectious diseases caused by viruses, bacteria, and other pathogens are common occurrences in the aquaculture industry, resulting in substantial economic losses and significantly im-pacting its sustainable development. 5 As aquaculture plays a vital role in global food security, understanding and managing the factors influencing fish health, such as gut microbiota dynamics during infections, contribute to ensuring a stable and secure food supply.…”
Section: Introductionmentioning
confidence: 99%